Utilize technical elements in the novel "Ibn Soula" by Ali Al-Mamari = توظيف العناصر الفنية في رواية "بن سولع" للكاتب علي المعمري - AL Hinai, Mohammed Ali Said; Ali, Asem Shehadeh Saleh; Hussein, Nasr El Din Ibrahim Ahmed (OCERINT International, 2020)
ناقشتْ هذه الدراسة التحليلية رواية "بن سولع" للأديب العُماني علي المعمري، التي بينت أسلوب المعمري في توظيف العناصر الفنية في الرواية. إذْ تعدُّ الرواية بناءً واحدًا لا يمكن فصل عناصرها؛ الشخصية، والزمانية، والحيّز المكاني، والأحداث، واللغة والأسلوب عندما تلتحم، عندئذٍ تحتاج إلى بحث إجرائي لاستخراج مكنوناته الكامنة في أعماقه، لتبيّن حقيقة التاريخ الدفين الذي شهدته تلك المنطقة. تهدف الدراسة: مناقشة توظيف العناصر الفنية في الرواية، وتوظيف الشخصية تاريخياً، والزمن في السرد الروائي، والحيّز، وتوظيف الوصف، وأخيراً توظيف اللغة والأسلوب. ومن خلال المنهج التحليلي، والمنهج الاستقرائي الوصفي؛ بينتْ نتائج الدراسة: اهتمام الكاتب في وصف الصراع، ومعاناة الشعوب في الإمارات، عمان، قطر، البحرين، السعودية، الكويت؛ سواء بسبب حكامها أم أطراف خارجية معادية. عرض الكاتب التاريخ العماني من جميع أبوابه؛ التاريخ السياسي والصراع الداخلي بين حكومة مسقط وعمان، والإمامة، والصراع حول "واحات البريمي" المتنازع عليها بين السعودية وعمان والأمارات. تجلت لنا شخصية الراوي في مخالفته للمعتقدات الخاطئة في المجتمع. ********************************************************** This analytical study discussed the novel "Bin Soula" by the Omani writer Ali Al-Maamari, which showed Al-Maamari's method of employing the artistic elements in the novel. As the novel is one building whose elements cannot be separated; Personality, temporality, spatial space, events, language and style when combined, then you need procedural research to extract its potentials deep within it, to show the truth of the hidden history that this region has witnessed. The study aims to: discuss the employment of artistic elements in the novel, the employment of personality historically, the time in narrative narration, space, the employment of description, and finally the language and style. Through the analytical method and the descriptive inductive approach; The results of the study showed: the writer's interest in describing the conflict and the suffering of peoples in the Emirates, Oman, Qatar, Bahrain, Saudi Arabia, Kuwait; Whether because of its rulers or hostile external parties. The author presented Omani history in all its chapters; Political history and internal conflict between the government of Muscat and Oman, the Imamate, and the struggle over the disputed Buraimi Oasis between Saudi Arabia, Oman, and the United Arab Emirates. The narrator's character was revealed to us in contradiction with wrong beliefs in society.